Differential Levels and Phosphorylation of Type 1 Inositol 1,4,5-Trisphosphate Receptor in Four Different Murine Models of Huntington Disease - Post, Joakim Iver; Leergaard, Trygve B.; Ratz, Veronika; Walaas, S. Ivar; von Hörsten, Stephan; Nissen-Meyer, Lise Sofie H. (Journal of Huntington's Disease, 2019)
Background: The intracellular ion channel type 1 inositol 1,4,5-trisphosphate receptor (IP(3)R1) releases Ca-2(+) from the endoplasmic reticulum upon stimulation with IP3. Perturbation of IP(3)R1 has been implicated in the development of several neurodegenerative disorders, including Huntington disease (HD).
CRIS-Team WoS Importer:2019-09-13